Radio frequency identification (RFID) based plate recognition for registered vehicle in UMP - Nur Aliaa, Mohd Ezanee (2012)
Recent advances technology in world of computer resolve the difficulty of recognition.Based on technology of Radio-Frequency (RFID) has enhanced a project of plate recognition for registered vehicle specially proposed to Universiti Malaysia Pahang.The scopes of work is study and develop a passive tag RFID system in detection of RFID Reader from input to output composed of hardware, database development and software programming Visual Basic.Net.Method and implementation conducted by stages due to the system requirements needed.RFID Plate Recognition solves the problems of unauthorized vehicle entering campus of UMP without inspection and come out with a number of statistics vehicle check-in and check-out day-by-day.